The Influence Of Village Apparatus Competency And Accountability On Village Financial Performance With Government Internal Control System (SPIP) As A Moderating Variable (Study In Villages In Biru-Blue District Deli Serdang District) - Sutan Amien Riyadi Siregar; Irfan; Eka Nurmala Sari (SEAN Institute, 2023)
The research aims to determine and examine the effect of: (1) village apparatus competence on village financial performance; (2) accountability for village financial performance; (3) the government's internal control system moderates the effect of village apparatus competence on village financial performance and (4) the government's internal control system moderates the effect of accountability on village financial performance. The research population is village officials who carry out village financial performance in Sibiru-biru District with a sample of 60 people from 10 villages. The research method is a quantitative method with Smart-PLS analysis. The results of the study concluded: (1) the competence of the village apparatus has an influence on village financial performance in Biru-Biru District, Deli Serdang Regency by 0.258 and it is stated that the proposed hypothesis is acceptable; (2) accountability has an influence on village financial performance in Biru-Biru District, Deli Serdang Regency by 0.251 and it is stated that the proposed hypothesis is acceptable; (3) the government's internal control system moderates the competence of village apparatus on village financial performance in Biru-Biru District, Deli Serdang Regency, which is 0.123 and the hypothesis stated is acceptable and (4) the government's internal control system moderates accountability for village financial performance in Sibiru-biru of Deli Serdang Regency is 0.251 and it is stated that the proposed hypothesis is acceptable. Overall, the results of the study show that village financial performance is influenced by the competence of village officials and the accountability of village officials moderated by the government's internal control system by 0.609 = 60.9%; while the remaining 39.1% is determined by other factors.